Dakwah Era Digital: Ajakan Al-Quran untuk Antisipasi Pengaruh Negatif Media Sosial TikTok - Hasan Basri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The presence of social media, especially TikTok, has changed people's behavior in their interactions with one another. The posting of video content on TikTok has an appeal. The focus of the study is on the power of preaching through the TikTok social media platform and its correlation with Quranic verses about enjoining good and forbidding wrong. Qualitative research method, presented descriptively. The study results show that TikTok has a significant influence on the dissemination of information and is effective in influencing the audience. The delivery of messages through video recordings accompanied by narration or oration has a charm that other media lack. Islam encourages its followers to adapt in spreading the message of da'wah. Islam positions every Muslim as a preacher. The Qur'an recommends three aspects of da'wah material (content) to the public to counteract the negative influence of social media, namely aqeedah, worship, and morals.